THE NEW LOOK AT PREVENTION OF ATOPIC DERMATITIS IN CHILDREN’S EARLY AGE - E. V. Dudnikova; N. N. Kobzeva; E. S. Prihodskaja (Медицинский вестник Юга России, 2013)
The article provides scientific data on pathogenetic mechanisms of atopic dermatitis formation with regard to the influence of microorganisms of the gastro-intestinal tract on the formation of immunity in infancy; the role of breastfeeding in the prevention of atopy is emphasized.